The Dominant Effect of Electronic Service Quality Attributes on Affective, Conative, and Action Electronic Customer Loyalty on Shopee E-Commerce Users in East Java - Nurul Maziyah; Prima Vitasari (Universitas Airlangga, 2022)
The high value of e-commerce business transactions which reached more than forty four billion US Dollars caused e-commerce companies to compete fiercely. Shopee is an example of a company that has successfully taken advantage of e-commerce business opportunities in Indonesia. Shopee as e-commerce with the most visitors currently has to face competition in its business scope. One way to face competition is to pay attention to the quality of its services (e-servqual). The purpose of this study is to analyze the indicators that have the most influence on the electronic service quality variable in maintaining affective, conative, and action e-customer loyalty on e-commerce users . Shopee in East Java by making modeling using Structural Equation Modeling . The sampling technique was carried out by purposive sampling, which was selected by Shopee users in various cities in East Java. The number of samples that are taken as much as 393 respondents. The attributes of the quality of electronic services in this study include efficiency, fulfillment, privacy, responsiveness, compensation and contact. From the results of the research, it is found that the indicators that give the greatest contribution to the diversity of the quality of electronic services are privacy , responsiveness , and contact . In addition, the relationship between e-servqual variables with affective, conative, and action customer loyalty , among others: e-servqual has a significant direct relationship and has a positive effect on affective E-loyalty, e-servqual has a significant direct and indirect relationship and has a positive effect on conative e-loyalty, e-servqual has a significant direct and indirect relationship and has a positive effect on action e-loyalty, affective e-loyalty has a significant direct and positive effect on conative e-loyalty, and affective e-loyalty has a significant direct relationship and has a positive effect on action e-loyalty.